Applying the EDPS Method to the Research into Thermophysical Properties of Solid Wood of Coniferous Trees - Ľuboš Krišťák; Rastislav Igaz; Ivan Ružiak (Advances in Materials Science and Engineering)
The results of using the EDPS (extended dynamic plane source) method to determine thermophysical properties of solid wood of coniferous trees growing in Slovakia with 0% and 12% equilibrium moisture content are presented in the paper. Solid wood of two different tree species: Norway spruce (Picea abies L.) and Scots pine (Pinus sylvestris L.) was used in the research. The research was carried out independently in three anatomical planes. Coefficients of thermal conductivity, thermal diffusivity, and specific heat capacity were determined following the research. Comparing the research results to the values determined by other authors and already published models to calculate individual parameters, the fact that the data gathered using the EDPS method can be accepted in case of all studied thermophysical properties can be stated.